Perpindahan dan hubungan semasa Orang Cam - Mohamad Zain Musa, (Universiti Kebangsaan Malaysia, 2008)
The Cham community is a component of the population of the kingdom of Champa proven to have existed from the year 192 to 1835. Throughout its history, some of the Cham people left their homeland in search of safety in neighboring countries, including Cambodia. This article attempts to discuss not only the various factors causing their emigrations, started in the tenth century, but also ways they settled in Cambodia, Vietnam, Laos, Malaysia, Autralia, France, the United States and some other countries, and lastly highlights the means they organize themselves internationally